Relationship between high-sensitivity C reactive protein and the risk of gallstone disease: results from the Kailuan cohort study - Tong Liu; Wenqiang Li; Sarah Tan Siyin; Nan Yao; Ning Duan; Guoshuai Xu; Jun Qu; Siqing Liu (BMJ Open)
Objectives Gallstone disease (GSD) can be caused by various health and clinical factors such as obesity, dyslipidaemia and an unhealthy diet, all of which are associated with higher high-sensitivity C reactive protein (hs-CRP) concentrations. Whether hs-CRP represents an independent risk factor for GSD is still unclear. We prospectively investigated hs-CRP in relation to the occurrence of GSD based on the Kailuan study.Study design Prospective cohort study.Setting The Kailuan cohort study was conducted in Tangshan City in northern China.Participants 95 319 participants who were free from GSD were recruited in this study. Epidemiological data, anthropometric parameters and biochemical data of participants were collected.Primary and secondary outcome measures Cox proportional hazards regression models were used to evaluate the association between hs-CRP concentrations and the risk of GSD after adjustments for potential confounders.Results During the mean 7.58 years of follow-up among 95 319 participants, 4205 participants were identified as newly diagnosed with GSD or having undergone cholecystectomy for cholelithiasis. Compared with the hs-CRP<1 mg/L group, elevated hs-CRP concentrations were significantly associated with higher risk of GSD with the corresponding HR of 1.11 (95% CI 1.03 to 1.19), 1.12 (95% CI 1.04 to 1.22) in the 1≤hs-CRP≤3 mg/L and hs-CRP>3 mg/L group, respectively. The multivariate model which included hs-CRP not only had a better line of fitness but also had better predictive values to help identify new cases of GSD during follow-up.Conclusion Elevated hs-CRP concentration is an independent risk factor for new-onset GSD among the Chinese population.Trial registration number ChiCTR-TNC-11001489.